Strategi Efektif dalam Evaluasi Pembelajaran Berbasis Kompetensi: Kajian Literature Review - Harahap, Nur Adawiyah; Zahra, Karina; Simamora, Vailimlim; Simatupang, Simeon Adrian; Dalimunthe, Muhammad Bukhori (CV. Rayyan Dwi Bharata, 2025)
This article aims to identify in depth the effective strategies in competency-based education evaluation. By using effective evaluation strategies, not only will the quality of learning improve, but students will also be better prepared to face real-world challenges with adequate skills. This study uses a literature review method, which aims to examine and analyze various scientific sources regarding effective strategies in competency-based learning evaluation. The results of this study indicate that evaluation in learning has a very important role in assessing the extent to which students have achieved the competencies set out in the curriculum. Based on previous research, it can be seen that implementing technology will help teachers identify student learning patterns and adjust evaluation strategies to better suit individual needs, so that competency-based evaluation becomes more accurate.